The presentation secrets of Steve Jobs : how to be insanely great in front of any audience - Gallo, Carmine (McGraw-Hill, 2010)
Whether he's introducing the new iPhone or delivering a keynote presentation, Steve Jobs electrifies audiences with his style and showmanship. He doesn't just convey information in his presentations; he tells a story, paints a picture, and shares a vision. He gives his audience a transformative experience that is unique, inspiring and unforgettable. Now you can do it too, by learning the specific techniques that have made Jobs the most captivating communicator on the world stage. Using Job's legendary presentations as a blueprint, communication-skills coach Carmine Gallo has mapped out a ready-to-use framework of presentation secrets to help you plan, deliver, and refine the best presentation of your life